Comparing return to play protocols after sports-related concussion among international sporting organisations - Prock, M.; O`Sullivan, D. M.; Tiernan, S. (The Physician and Sportsmedicine, 2024)
Background Return to play (RTP) protocols are an important part of recovery management following a sport-related concussion (SRC) and can prevent athletes from returning to competition too early and thereby avoid prolonged recovery times. To assist sporting organizations in the development of RTP guidelines, the Concussion in Sports Group (CISG) provides scientific-based recommendations for the management of SRC in its consensus statement on concussion in sport.